2021
DOI: 10.3389/fdmed.2021.667365
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Salivary Metabolites by Nuclear Magnetic Resonance Before and After Oral Mucosa Cleaning of Infants in the Pre-dental Period

Abstract: The aim of the present study was to verify if a protocol for cleaning the oral cavity of infants in the pre-dental period can reduce extrinsic salivary metabolites observed through Nuclear Magnetic Resonance (NMR). A cross-sectional clinical study with a convenience sample was conducted, and infants were recruited at the UFRJ Pediatric Dentistry Clinic. Participants who had used antibiotics and/or antifungals up to 3 months before and whose legal guardians did not consent or sign the Informed Consent Form were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In 2021, Letieri et al [ 16 ] conducted a cross-sectional clinical investigation coupled with a convenience sample in order to assess the influence of oral mucosa cleansing on the salivary metabolic profiles of infants in their pre-dental periods (mean age 3.8 months); these profiles were acquired through 1 H NMR analysis on a 500 MHz spectrometer. Perhaps unsurprisingly, these researchers found that this oral cleansing approach, which involved the application of gauze moistened with filtered water, resulted in a decrease in glucose, lactose, further sugars, acetate, alanine and lactate, which may all arise from dietary sources anyway.…”
Section: Scientific and Clinical Benefits Offered By Salivary Metabol...mentioning
confidence: 99%
“…In 2021, Letieri et al [ 16 ] conducted a cross-sectional clinical investigation coupled with a convenience sample in order to assess the influence of oral mucosa cleansing on the salivary metabolic profiles of infants in their pre-dental periods (mean age 3.8 months); these profiles were acquired through 1 H NMR analysis on a 500 MHz spectrometer. Perhaps unsurprisingly, these researchers found that this oral cleansing approach, which involved the application of gauze moistened with filtered water, resulted in a decrease in glucose, lactose, further sugars, acetate, alanine and lactate, which may all arise from dietary sources anyway.…”
Section: Scientific and Clinical Benefits Offered By Salivary Metabol...mentioning
confidence: 99%
“…A mixture of 540 μL of saliva supernatant from the respective subjects plus 60 μL of pH 7 phosphate buffer was prepared, containing 99.8% (to provide a field-frequency lock) and 20 µM of 4,4-dimethyl-4-silapentane-1-sulfonic acid (DSS) (for chemical shift referencing, δ = 0.00 ppm) [ 14 , 29 ]. The spectra acquisitions (0–12 ppm) were performed in a standardized way, with a pre-established receiver gain and number of scans (1024 scans) and a calculated pulse time and signal/noise ratio.…”
Section: Experimental Designmentioning
confidence: 99%
“…Data were subjected to correction and base alignment using the software Topspin 4.1.4 (Bruker Biospin program, Rheinstetten, Germany). 1 H- 1 H total correlation (TOCSY) experiments were also conducted, with acquisition parameters of 2048 × 256 complex points, a spectral width of 12,019 Hz in each dimension, and a mixing time of 70 ms [ 8 , 14 ]. Spectra and spectral regions that could not be corrected for phase and baseline were excluded from the analyses.…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations